2022
DOI: 10.1177/14779714221135655
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of the Behavioural Intention of Open Distance Learning Students to Use Digital Tools and Resources for Learning in Nigeria

Abstract: This study investigated determinants of the behavioural intention of Open Distance Learning (ODL) students to use digital tools and resources for learning in Nigeria. The study utilized an online questionnaire to gather data from 522 ODL students from an ODL institution in Nigeria. The Unified Theory of Acceptance and Use of Technology (UTAUT) was the main framework used for the analysis in which attitude was included as an additional variable to seek out a much better model capable of improving the understand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…The learning materials were suitable for the course, helpful for their learning, and easily understood. According to Itasanmi [25], educational resources had a significant relationship with students' satisfaction with ODL programme. This finding was also similar to Rajadurai et al [24], whereby learners were satisfied with their usage of learning materials.…”
Section: Students' Satisfaction With Open and Distance Learningmentioning
confidence: 99%
See 2 more Smart Citations
“…The learning materials were suitable for the course, helpful for their learning, and easily understood. According to Itasanmi [25], educational resources had a significant relationship with students' satisfaction with ODL programme. This finding was also similar to Rajadurai et al [24], whereby learners were satisfied with their usage of learning materials.…”
Section: Students' Satisfaction With Open and Distance Learningmentioning
confidence: 99%
“…They were very satisfied that the lecturers were always ready to answer their questions and used strategic manner to help students learn. Itasanmi [25] explained that teaching and learning experiences contributed to general satisfaction in ODL programme. Other than that, Agbanu and Ahiase [26] also supported that the instructor's performance and their interaction with students significantly contributed to the students' satisfaction.…”
Section: Students' Satisfaction With Open and Distance Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of these challenges are resolved when institutions provide proper technical assistance, such as laptops, mobile phones, and technical support services, and students gain a higher sense of confidence in the system, which ultimately boosts their satisfaction with educational programs (Itasanmi and Oni, 2021). Technical support is an integral part of any open or remote education system.…”
Section: Technical Support and Students' Satisfactionmentioning
confidence: 99%
“…It encompasses informational assistance, institutional assistance, academic assistance, and prompt feedback to students (Aftab et al, 2019). Recent research by Aftab et al (2019) and Itasanmi and Oni (2021) reveals that technical support services are the most important factor influencing students' satisfaction in open distance learning programs. As a result, it is concluded that technical assistance has a favourable effect on student satisfaction.…”
Section: Technical Support and Students' Satisfactionmentioning
confidence: 99%